Religious Diversity and Inclusion: Policy and Accommodation Practices in British Columbia’s Secular School System - Jacquet, Marianne; D'Amico, Laura (Canadian Journal of Education/Revue canadienne de l’éducation, 2016)
The religious diversity of students and staff within a secular school system may sometimes create tensions. To better understand the possible issues generated by and practical accommodations made with respect to these tensions, interviews were conducted at the district level with key administrators in metropolitan school districts in British Columbia. These interviews aimed to document existing policy related to religious diversity in schools, and understand how school districts address issues related to religious values or beliefs, which may conflict with existing educational values, especially as they relate to curriculum.